Exploitation of the Ugi–Joullié Reaction in the Synthesis of Libraries of Drug-Like Bicyclic Hydantoins - Firth, James D.; Zhang, Rong; Morgentin, Rémy; Guilleux, Rachel; Kalliokoski, Tuomo; Warriner, Stuart; Foster, Richard; Marsden, Stephen P.; Nelson, Adam (Synthesis, 2015)
A general and efficient method for the synthesis of drug-like fused bicyclic hydantoins is reported. An Ugi–Joullié reaction/cyclisation sequence was exploited as the key complexity-generating process in which trifluoroacetic acid was employed as synthetic equivalent for chloroformic acid. Exemplar diversification of the bicyclic scaffolds was performed to enable subsequent translation to the synthesis of large small molecule libraries, leading to the production of >1000 compounds for addition to the screening collection of the European Lead Factory.
Keywords: multicomponent reactions; scaffolds; libraries; Ugi reaction; hydantoin